Hiệu ứng điện ly plasma trong quá trình điều chế dung dịch nano bạc bằng dòng một chiều cao áp - Hùng, Nguyễn Đức; Thùy, Nguyễn Minh; Hải, Nguyễn Thanh; Trang, Phan Thị; Trụ, Nguyễn Nhị (Vietnam Journal of Chemistry, 2014)
Implementation of the electrochemical reaction of silver electrode in double distilled water by DC high-voltage will occur the metal dissolution process on the anode and hydrogen on the cathode comply with Faraday’s law. Also on the electrodes appear luminescent effects due to the formation of plasma on cathode and on anode. The Non-Faraday process of water electrolysis by plasma will generate the large amounts of hydrogen on electrodes contribute to the reduction of silver ions to formation of nanoparticle in the solution. Keywords: Electrolysis plasma, Silver nanoparticle, Nano solution, DC high voltage, Hydrogen Formation